1976
DOI: 10.1177/001391657684005
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Orientation in a Subway System

Abstract: The absence of a clear structural legibility within the New York City subway system tends to make its users dependent on other informational aids about its structural design and operations-such as signs, announcements, and especially the official New York City subway map and guide. The effectiveness of the New York City subway guide was tested by assigning 20 Ss a travel route which consisted of four trip-segments of varying difficulty. Of the total 80 trip segments, only 37 were traveled via acceptable (as de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1976
1976
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 3 publications
0
18
0
Order By: Relevance
“…Out-of-vehicle travel time valuation also has been found to be influenced by transit user characteristics, such as users' familiarity with the city, transit system, given line, and given stop, as well as the physical condition of the traveler, whether the traveler is late for work or an appointment, and whether the traveler can otherwise use the waiting time productively (Bronzaft, Dobrow, and O´Hanlon 1976;Reynolds and Hixson 1992;Woyciechowicz and Shliselberg 2005;Lacy and Bonsall 2001;Dziekan, Schlag, and Jünger 2004;Dziekan and Vermeulen 2006;Dziekan and Kottenhoff 2007;Dziekan 2008;Balcombe et al 2004). …”
Section: Previous Research and Conceptual Frameworkmentioning
confidence: 99%
“…Out-of-vehicle travel time valuation also has been found to be influenced by transit user characteristics, such as users' familiarity with the city, transit system, given line, and given stop, as well as the physical condition of the traveler, whether the traveler is late for work or an appointment, and whether the traveler can otherwise use the waiting time productively (Bronzaft, Dobrow, and O´Hanlon 1976;Reynolds and Hixson 1992;Woyciechowicz and Shliselberg 2005;Lacy and Bonsall 2001;Dziekan, Schlag, and Jünger 2004;Dziekan and Vermeulen 2006;Dziekan and Kottenhoff 2007;Dziekan 2008;Balcombe et al 2004). …”
Section: Previous Research and Conceptual Frameworkmentioning
confidence: 99%
“…Often, the reported alternatives were simple variations on the already used multi-modal trip, whereby the rail component, which was the primary part of the multi-modal trip made by the travellers surveyed, was constant and only the mode for the feeder trips varied (Hoogendoorn-Lanser 2005). Bronzaft et al (1976) analysed the nature of the orientation problems of the user of the New York City metro and evaluated a metro guide as an aid in this orientation. They found that the subjects, who had to make several metro trips, relied on their limited metro experience and selected ''indirect'' routes rather than looking for more acceptable ones (Bronzaft et al 1976).…”
Section: Introductionmentioning
confidence: 99%
“…Bronzaft et al (1976) analysed the nature of the orientation problems of the user of the New York City metro and evaluated a metro guide as an aid in this orientation. They found that the subjects, who had to make several metro trips, relied on their limited metro experience and selected ''indirect'' routes rather than looking for more acceptable ones (Bronzaft et al 1976).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, only a few studies have examined orientation and navigation in cities. Bronzaft, Dobrow, and O'Hanlon (1976) conducted an experimental study that demonstrated the difficulties people may have. The subjects participating in the study were asked to make trips through the New York City subway system.…”
Section: Cognitive Maps Of Cities Spatial Orientation and Navigationmentioning
confidence: 99%